Association between homocysteine, C-reactive protein, lipid level, and sleep quality in perimenopausal and postmenopausal women. Issue 51 (23rd December 2021) - Zhang, Hongyan; Wang, Qianwen; Deng, Miao; Chen, Yijie; Liu, Wenhua; Huang, Jian; Zhang, Zhifen
Abstract : Abstract: This study aimed to investigate the correlation between homocysteine (HCY), C-reactive protein (CRP), lipid levels, and sleep quality in perimenopausal and postmenopausal women. We collected data from 217 patients (perimenopause and postmenopausal) who visited the gynecological endocrine outpatient department of our hospital between January 2017 and January 2019. The quality and patterns of sleep were measured using the Pittsburgh Sleep Quality Index, and relationships between HCY, CRP, lipid levels, and sleep quality were analyzed according to a Pittsburgh Sleep Quality Index ≥ 8. There were significant differences in age, education level, and occupation among patients with different levels of sleep quality ( P < .05). HCY, CRP, total cholesterol, triglyceride, and low-density lipoprotein levels were significantly higher in patients with poor sleep quality than in those with good sleep quality ( P < .05). Age, education level, occupation, HCY, CRP, and lipid levels (total cholesterol, triglyceride, low-density lipoprotein, high-density lipoprotein) were all significant influencing factors for sleep quality in perimenopausal and postmenopausal women (all P < .05). After adjusting for age, education level, occupation, HCY, and CRP levels were all significant and independent risk factors for sleep quality in perimenopausal and postmenopausal women (all P < .05). Levels of HCY, CRP, and lipids were significantly correlated with sleep quality in perimenopausal and postmenopausal women. HCY and CRP were identified as independent risk factors for sleep quality in perimenopausal and postmenopausal women, thus providing theoretical support for the clinical improvement of sleep quality.